Gendered and classed homelessnessA life-history analysis on displaced survival in Lisbon - Saila-Maria Saaristo (Cidades, Comunidades e Território)
This article examines the gendered and classed dynamics of homelessness and displacements in Portugal. I use the lens of displaced survival to bring light to the complex web of relations that promote the housing exclusion of low-wage single mothers. I show how these families, expelled from housing programmes and unable to afford housing in the private rental sector, are left to suffer from a cycle of displacements, leading to accentuated poverty and dispossession, which also leads to over-generational perpetuation of poverty. Methodologically the study draws from life-history interviews and policy analysis, conducted from 2017 to 2019 in Lisbon. In addition to being exploited within paid and unpaid labour and having to pay an unaffordable rent, displacements and evictions exacerbate the dispossession and poverty of these families, given that their specific conditions as low-income single mothers are not recognised within the policy responses.